Recent Advances in Local Anesthesia Techniques in Pediatric Dentistry - Oğuzhan Güler; Burcu Nihan Yüksel (Journal of Gazi University Health Sciences Institute, 2026)
Effective pain control in pediatric dentistry is not only essential for the success of dental procedures but also plays a key role in shaping children's attitudes toward dental care. In recent years, several innovative anesthesia delivery systems have emerged, aiming specifically to reduce the discomfort and emotional stress associated with injections. Computer-controlled local anesthetic delivery systems such as The Wand, QuickSleeper, and SleeperOne offer precise control over the flow rate and pressure of anesthetic solutions. These systems provide a more comfortable experience for pediatric patients although factors such as cost and ease of use still present certain challenges in clinical adoption. Devices like VibraJect and DentalVibe based on the Gate Control Theory, they use vibration to minimize pain, which suggests that non-painful input can suppress pain sensations. These tools have shown promising results in reducing needle-related discomfort and anxiety in children during injections. These advancements signal a shift in the approach to local anesthesia in pediatric dentistry from simply blocking pain to improving the overall patient experience and fostering trust in dental care from an early age. As these technologies continue to evolve, further research could pave the way for significantly more effective and child-friendly pain management strategies in the future.